Indications for Induction of Labour: A Prospective Analysis (Health Renaissance, 2011)
Setting: Department of Gynaecology & Obstetrics, B P Koirala Institute of Health Sciences, Dharan, Nepal. Objective: The study was conducted to find out the different indications of induction of labour as well as cesarean delivery rate, fetal and neonatal morbidity associated with induction of labour. Methods: A prospective observational study was conducted at obstetric unit of B.P Koirala Institute of Health Sciences, a tertiary care centre in eastern Nepal .The study enrolled 262 consecutive patients from April2008 to august 2008 recruited to induction of labour according to the standard practiced in the institute. Dinoprostone gel was used as induction agent in all the cases, the patients were monitored in labour according to hospital protocol, cesarean was performed for routine indications. Fetal morbidity was assessed in terms of NICU admissions & 5 min Apgar scores. Results: 62% of patients were unbooked. Prolonged pregnancy (62.8%) and hypertensive disorders (18.7%) were the common indications for induction of labour. Cesarean delivery rate was 47.2% and NICU admission was 5.3%. Conclusion: Prolonged pregnancy and hypertensive disorders are the common indications for induction of labour. Standard labour management protocol has to be followed to avoid unnecessary cesarean delivery and have a better neonatal outcome. Keywords: induction of labour; cesarean delivery; post dated pregnancy DOI: 10.3126/hren.v8i2.4423 Health Renaissance, May-Aug 2010; Vol 8 (No.2):114-116